Kenya’s National Action Plan on antimicrobial resistance: measuring implementation progress - Mukoko, Joseph; Wesangula, Evelyn; Gitonga, Nkatha; Kusu, Ndinda; Odhiambo, Cynthia; Tanui, Emmanuel; Azegele, Allan; Ndanyi, Romona; Joshi, Mohan P.; Hafner, Tamara; Konduri, Niranjan (Frontiers in Tropical Diseases, 2025)
Kenya has established a multisectoral national action plan (NAP) on antimicrobial resistance (AMR), which provides a common framework for action by all stakeholders from different sectors in implementing AMR containment activities. Monitoring and evaluation (M&E) of the NAP-AMR has been weak, however, necessitating the development of a multisectoral M&E framework in 2021. Using this M&E tool, Kenya’s highest level technical body charged with containing AMR—the National Antimicrobial Stewardship Interagency Committee (NASIC)—led a review of the NAP-AMR (2017–2022) implementation progress at the national and county levels. The review showed that 16 out of 47 counties had established County Antimicrobial Stewardship Interagency Committees mirroring the NASIC and that 93% (38 out of 41) of the activities listed in the NAP-AMR (2017–2022) and the 2021 M&E framework for human health were either completed or ongoing (compared to 64% [28 out of 44] that were completed or ongoing in the animal and crop sectors). Key challenges identified for the implementation of the NAP-AMR included lack of adequate funding; difficulties in effective collaboration across and within relevant sectors; weak laboratory-clinical interface; erratic supply of laboratory reagents, equipment, and supplies leading to underutilization of microbiology laboratories; and poor internet connectivity at the various facilities negatively affecting transmission of AMR data to the national level. Major learnings and recommendations from the review—strengthening governance arrangements at the national and county level; costing of the NAP-AMR; and ramping up advocacy efforts to political leadership to gather further support for actions on AMR—were integrated into the next iteration of the NAP-AMR (2023–2027), which was released during the World AMR Awareness Week in November 2023. Strengthening the process for monitoring the implementation of the NAP-AMR and cascading that process to the subnational (county) level were identified as critical for a robust operationalization of NAP-AMR.